EVALUASI KOMPETENSI AUDITOR INSPEKTORAT KOTA KENDARI DALAM MELAKSANAKAN PEMERIKSAAN - Anto, La Ode; Hadisantoso, Erwin; Nugrawati, Ersita (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACTÂ This research is aimed to evaluation of the competency auditor Kendari City Inspectorate the implement the audit. Data collection tekhniques used in research by using questionnaire, interview and documentation. As for sample in this research are auditor and PPUPD in Kendari City Inspectorate that as many as 28 respondents. Data sources used the primary data and data secondary. The methods used data analysis the descriptive. The results of this research indicate that the competency auditor in Kendari City Inspectorate is adequate. This is evidenced by the spread of questionnaires that answered by the respondents unde five incator, namely the background of education, competence technically, the certificate JFA and education and training sustainable, the experience of the audit and skill. The fifth indicator that can increase the competencyâs auditors.Key words :Â  evaluation, competency, auditors, auditing